2009 IEEE International Conference on Rehabilitation Robotics 2009
DOI: 10.1109/icorr.2009.5209507
|View full text |Cite
|
Sign up to set email alerts
|

Developing a user interface for the iPAM stroke rehabilitation system

Abstract: The increasing population of older people is leading to growing healthcare demands. Stroke is the commonest cause of severe disability in developed countries leaving one third of patients with long term disability. Rehabilitation is the cornerstone of recovery. Lack of rehabilitation manpower resources can limit recovery of limb function. However, technology can assist rehabilitation staff to deliver greater intensity of treatment. Robotic systems such as the iPAM robot can provide semi-automated arm exercises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Jackson et al [ 39 ] reported that the feedback of end-users was invaluable in the development of the iPAM system and for future design improvements. This also applied to the interface development of the system [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jackson et al [ 39 ] reported that the feedback of end-users was invaluable in the development of the iPAM system and for future design improvements. This also applied to the interface development of the system [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stanford University has developed a robotic upper limb rehabilitation system based on the PUMA 500 and 600 industrial robots, which can assist stroke survivors in performing mirror movements of the affected and healthy sides of the upper limb [35] [36]. Some universities in Europe have also designed and developed various upper limb rehabilitation robot systems [37] [38] [39] [40]. However, studies have shown that some upper limb robots are not capable of performing wrist flexion and extension training, and these robots are expensive [41].…”
Section: Related Workmentioning
confidence: 99%
“…To design the software, elements of the Goal Directed Design (GDD) technique [18] were used, which is a user-centered technique of a similar nature to those implemented in [19], [20] that emphasizes researching the user's capabilities and understanding the user's goals in using the product. Key age-related characteristics of the user are changes in visual and cognitive ability, as well as in motor control [3].…”
Section: The Design and Evaluation Of An Activity Monitoring User Intmentioning
confidence: 99%